Carbon nanotube grafted polymer nano plugging agent, preparation method thereof and prepared drilling fluid

By reacting acrylic acid with amino-functionalized multi-walled carbon nanotubes and copolymerizing with acrylamide and octadecyldimethylallyl ammonium chloride, carbon nanotube graft polymer nanosealing agent was prepared, which solved the problem of poor dispersion stability of existing drilling fluid sealing agents in high temperature and high salt environments, and effectively sealing micro-nano pores and cracks in shale reservoirs.

CN119823334AActive Publication Date: 2025-04-15CHINA NAT PETROLEUM CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311322331.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

Existing drilling fluid sealing agents are difficult to maintain dispersion stability in high temperature and high salt environments, and cannot effectively seal micro-nano pores and cracks in shale reservoirs.

Method used

Carbon nanotube grafted polymer nanocapsule agent was prepared by reacting acrylic acid with amino-functionalized multi-walled carbon nanotubes to produce acrylic acid modified carbon nanotubes, and copolymerization with acrylamide and octadecyldimethylallyl ammonium chloride.

Benefits of technology

This nanosealer maintains good dispersion stability in high temperature and high salt environments, significantly improves mud shale inhibition and sealing properties, and can effectively seal micro-nano pores and cracks in shale reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823334A_ABST
    Figure CN119823334A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nanotube grafted polymer nano plugging agent, a preparation method thereof and a prepared drilling fluid, the preparation method comprises the following steps: S1, acrylic acid and amino-functionalized multi-walled carbon nanotubes in a mass ratio of 1: (0.1-0.2) are subjected to a reaction to generate acrylic acid modified carbon nanotubes; s2, acrylamide, the acrylic acid modified carbon nanotubes and octadecyl dimethyl allyl ammonium chloride are subjected to a copolymerization reaction according to the mass ratio of 25: (0.2-0.8): (1.2-2.0), and the carbon nanotube grafted polymer nano blocking agent is obtained. The carbon nanotube grafted polymer nano plugging agent comprises an amide group, a quaternary ammonium salt structure and an amino group, the micro-nano plugging capability of the plugging agent is enhanced, the inhibition capability on hydration expansion and dispersion of stratum shale is enhanced, and the plugging agent has good temperature resistance, salt resistance and dispersion stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oilfield chemicals in the petroleum industry, and specifically relates to a carbon nanotube grafted polymer nano plugging agent, a preparation method thereof and a drilling fluid prepared therefrom. Background Art

[0002] Shale gas is a clean and efficient new energy resource, and its shale reservoirs are prone to hydration. In order to effectively solve the problem of wellbore instability caused by shale hydration expansion and dispersion, plugging agents are needed. Shale reservoirs mostly show a low porosity (<10%), and most of them are nano-scale pores. Existing drilling fluid plugging agents mainly include asphalt, paraffin, polyols and mineral materials. The particle size of these drilling fluid plugging agents cannot reach below the micron level, and it is difficult to achieve effective plugging for tiny pores and micro-crack formations, especially mud shale formations. Therefore, in the process of shale gas drilling, it is crucial to develop nano plugging agents.

[0003] Carbon nanotubes can be used as plugging agents for water-based drilling fluids to control reservoir loss due to their excellent rheological, mechanical and thermal properties. However, carbon nanotubes are easy to curl and aggregate, and the high temperature and high salt environment of shale reservoirs further strengthen the tendency to aggregate. Therefore, the stability of nanocolloid solutions based on carbon nanotubes is poor, which limits their application in oil and gas fields. The addition of surfactants and stabilizers, such as polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylic acid and non-ionic surfactants, can improve the stability of carbon nanotubes in salt environments. However, the interaction between these chemicals and carbon nanotubes is weak, and it is difficult to achieve long-term stability of carbon nanotubes in high temperature and high salt environments.

[0004] Some existing technologies organically combine multi-walled carbon nanotubes with polymers to improve the plugging and dispersibility of multi-walled carbon nanotubes. For example, CN109825263A discloses a nano plugging agent for water-based drilling fluid, a preparation method thereof, and drilling fluid, which realizes a nano plugging agent that is uniformly dispersed at the nanoscale level in the drilling fluid and has a good plugging effect, and effectively plugs the micro- and nano-sized pores of the shale well wall. However, there are currently few varieties of nano plugging agents, and there is no nano plugging agent that has good shale inhibition.

[0005] Therefore, there is an urgent need to invent a carbon nanotube grafted polymer nano plugging agent that maintains good dispersion stability in a high temperature and high salt environment to meet the inhibition, plugging and environmental protection requirements of water-based drilling fluids during shale reservoir drilling. Summary of the invention

[0006] To solve the above technical problems, the purpose of the present invention is to provide a carbon nanotube grafted polymer nano plugging agent and its preparation method and prepared drilling fluid, so as to improve the dispersion stability of the nano plugging agent in a high temperature and high salt environment, and achieve shale inhibition and micro-nano pore plugging.

[0007] In order to achieve the above object, the present invention provides a method for preparing a carbon nanotube grafted polymer nano plugging agent, which comprises the following steps:

[0008] S1: reacting acrylic acid with amino-functionalized multi-walled carbon nanotubes to generate acrylic acid-modified carbon nanotubes; wherein the mass ratio of acrylic acid to amino-functionalized multi-walled carbon nanotubes is 1:0.1-0.2;

[0009] S2: copolymerizing acrylamide, the acrylic acid modified carbon nanotubes and octadecyl dimethyl allyl ammonium chloride to obtain the carbon nanotube grafted polymer nano plugging agent; wherein the mass ratio of acrylamide, the acrylic acid modified carbon nanotubes and octadecyl dimethyl allyl ammonium chloride is 25:0.2-0.8:1.2-2.0, preferably 25:0.3-0.6:1.4-1.8.

[0010] The invention grafts amino-functionalized multi-walled carbon nanotubes onto polymer molecules by a chemical method, and the obtained nano plugging agent has good dispersion stability, salt resistance, shale inhibition and plugging properties in drilling fluid.

[0011] The preparation of the carbon nanotube grafted polymer nano plugging agent of the present invention is divided into two steps. The first step is to react acrylic acid with amino-functionalized multi-walled carbon nanotubes (CNT-NH2) to generate acrylic acid-modified carbon nanotubes (CNT-AA); the second step is to use acrylamide, acrylic acid-modified carbon nanotubes (CNT-AA) and octadecyl dimethyl allyl ammonium chloride as polymerization monomers to synthesize grafted carbon nanotube polymers (CNT-HPAM) by aqueous solution monomer copolymerization.

[0012] The reaction synthesis route of acrylic acid-modified carbon nanotubes (CNT-AA) in S1 of the present invention is as follows:

[0013]

[0014] The reaction synthesis route of the carbon nanotube grafted polymer nano plugging agent (CNT-HPAM) in S2 of the present invention is as follows:

[0015]

[0016] According to a specific embodiment of the present invention, preferably, S1 of the method for preparing the carbon nanotube-grafted polymer nano plugging agent comprises the following steps:

[0017] (1) adding amino-functionalized multi-walled carbon nanotubes (CNT-NH2) and sodium dodecyl sulfate (SDS) to N,N-dimethylformamide (DMF) and dispersing by ultrasonication to obtain a carbon nanotube solution A;

[0018] (2) adding acrylic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) to N,N-dimethylformamide (DMF), adding hydrochloric acid dropwise to adjust the pH value of the solution to 4-6, and stirring thoroughly to dissolve, thereby obtaining acrylic acid solution B;

[0019] (3) The carbon nanotube solution A and the acrylic acid solution B are mixed and reacted to obtain a solid product, which is then filtered and washed to obtain the acrylic acid-modified carbon nanotubes (CNT-AA).

[0020] According to a specific embodiment of the present invention, preferably, in S1, the mass ratio of amino-functionalized multi-walled carbon nanotubes, acrylic acid, sodium dodecyl sulfate, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 0.1-0.2:1:0.1-0.4:0.05-0.1.

[0021] According to a specific embodiment of the present invention, preferably, the reaction temperature of step (3) is 0-5°C, and the reaction time is 8-10h.

[0022] According to a specific embodiment of the present invention, preferably, the dissolution process of step (2) is carried out at 0-5°C.

[0023] According to a specific embodiment of the present invention, preferably, the reagent used for washing in step (3) is ethanol.

[0024] According to a specific embodiment of the present invention, preferably, S2 of the method for preparing the carbon nanotube-grafted polymer nano plugging agent comprises the following steps:

[0025] (4) acrylamide (AM), the acrylic acid-modified carbon nanotubes (CNT-AA), octadecyl dimethyl allyl ammonium chloride (C 18 DMAAC) was dissolved in water, the pH value was adjusted to 8-10, nitrogen was introduced and ultrasonic dispersion was performed to obtain a dispersion;

[0026] (5) adding an initiator to the dispersion, continuing to pass nitrogen and stirring until the viscosity of the solution increases; then stopping stirring and passing nitrogen, and continuing the reaction to obtain a reaction solution;

[0027] (6) The reaction solution is heated, and an alkali solution is added to perform a hydrolysis reaction to obtain a gel product, and after washing and drying, the carbon nanotube grafted polymer nano plugging agent (CNT-HPAM) is obtained.

[0028] According to a specific embodiment of the present invention, preferably, in S2, the initiator is a mixture of potassium persulfate (K2S2O8) and sodium bisulfite (NaHSO3).

[0029] According to a specific embodiment of the present invention, preferably, in S2, the mass ratio of potassium persulfate, sodium bisulfite and acrylamide is 0.03-0.06:0.06-0.1:25.

[0030] According to a specific embodiment of the present invention, preferably, the reaction time in step (5) is 4-6 hours.

[0031] According to a specific embodiment of the present invention, preferably, in step (6), the reaction solution is heated to 70-90° C. and the hydrolysis reaction time is 4-6 h.

[0032] According to a specific embodiment of the present invention, preferably, in step (6), the alkali solution is sodium hydroxide and / or sodium carbonate.

[0033] According to a specific embodiment of the present invention, preferably, in step (6), the reagent used for washing is acetone.

[0034] According to a specific embodiment of the present invention, preferably, in step (6), the drying conditions are: drying at a temperature of 60-80° C. for 10-15 hours.

[0035] The present invention also provides a carbon nanotube grafted polymer nano plugging agent, which is obtained by the preparation method of the carbon nanotube grafted polymer nano plugging agent.

[0036] According to a specific embodiment of the present invention, preferably, the particle size distribution of the carbon nanotube grafted polymer nano plugging agent is between 16-451 nm.

[0037] The nanometer plugging agent in the present invention has a wider particle size distribution, ranging from 16 to 451 nm, and can plug shale formation pores of more sizes.

[0038] The present invention also provides a water-based drilling fluid, which contains the carbon nanotube grafted polymer nano plugging agent.

[0039] In the above-mentioned water-based drilling fluid, preferably, in terms of mass percentage (based on the total mass of the drilling fluid), the raw materials of the water-based drilling fluid include: 0.5-3% of the carbon nanotube grafted polymer nano plugging agent, 0.5-1.5% of bentonite, 0.5-1.5% of a viscosity enhancer, 1.0-2.0% of a fluid loss reducer, 0.5-1.5% of a pH adjuster, 2.0-4.0% of a lubricant, and the balance of water.

[0040] In the above water-based drilling fluid, preferably, the raw material of the water-based drilling fluid also includes a weighting agent, and the density of the water-based drilling fluid with the weighting agent added is 1.2-2.0 g / cm 3 .

[0041] When the carbon nanotube grafted polymer nano plugging agent of the present invention forms a water-based drilling fluid with drilling fluid chemical products such as water, bentonite, viscosity enhancer, fluid loss reducer, pH adjuster, lubricant, weighting agent, etc., it has excellent plugging ability, good compatibility, strong inhibition, non-toxicity, and meets environmental protection requirements. The present invention examines the compatibility of the nano plugging agent with other drilling fluid materials, and the formed water-based drilling fluid has excellent performance and good plugging effect.

[0042] The technical solution provided by the present invention has the following beneficial effects:

[0043] Compared with commercially available amino-functionalized multi-walled carbon nanotubes and common fiber plugging agents, the carbon nanotube grafted polymer nano plugging agent of the present invention contains an amide group, a quaternary ammonium salt structure and an amino group, which enhances the micro-nano plugging ability of the plugging agent while enhancing the ability to inhibit the hydration expansion and dispersion of shale in the formation, and has good temperature and salt resistance and dispersion stability. In some specific embodiments, the nano plugging agent of the present invention can be stable for 28 days in saturated brine and simulated formation water environments at 120°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Infrared spectra of the three nanomaterials CNT-NH2, CNT-AA-1, and CNT-HPAM-1 in Example 1;

[0045] Figure 2 The Zeta potential changes of the three solutions after the CNT-HPAM-2 material of Example 2 was added to deionized water, saturated brine and simulated formation water respectively. DETAILED DESCRIPTION

[0046] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0047] Example 1

[0048] This embodiment provides a carbon nanotube grafted polymer nano plugging agent, and the preparation method thereof is as follows:

[0049] (1) 40 ml of DMF solvent was added, 0.1 g of CNT-NH2 and 0.4 g of SDS were added, and the mixture was stirred and ultrasonically dispersed for 2 h to obtain solution A; (2) 20 ml of DMF solvent was added, 1.0 g of acrylic acid and 0.1 g of EDC·HCl were added, 1 M dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 4, and the mixture was stirred in an ice-water bath at 0-5°C for 3 h to fully dissolve the mixture, to obtain solution B; (3) the above solution A and solution B were mixed, and the mixture was stirred in an ice-water bath at 0-5°C for 10 h, and then filtered and washed with anhydrous ethanol for several times, and dried to obtain acrylic acid-modified carbon nanotubes CNT-AA-1; (4) 25.0 g of AM, 0.2 g of CNT-AA-1 and 1.2 g of C were added in a three-necked flask. 18 DMAAC was completely dissolved in 100 ml of deionized water, and an appropriate amount of Na2CO3 was added to adjust the solution pH to 8. Nitrogen was passed through the mixture, and the mixture was stirred at 40°C and ultrasonically dispersed for 2 h. (5) 0.06 g K2S2O8 and 0.1 g NaHSO3 were added, and nitrogen was continued to be passed through and stirred until the viscosity of the solution increased significantly. Stirring and nitrogen were stopped, and the reaction was continued for 6 h. (6) The mixture was heated to 85°C and hydrolyzed with a mixture of NaOH and Na2CO3 for 4 h to obtain a black gel product. The product was granulated and repeatedly washed with acetone until a black solid was precipitated. The carbon nanotube grafted polymer nanoblocking agent CNT-HPAM-1 was obtained after drying at 70°C for 12 h.

[0050] Example 2

[0051] This embodiment provides a carbon nanotube grafted polymer nano plugging agent, and the preparation method thereof is as follows:

[0052] (1) 40 ml of DMF solvent was added, 0.1 g of CNT-NH2 and 0.2 g of SDS were added, and the mixture was stirred and ultrasonically dispersed for 2 h to obtain solution A; (2) 20 ml of DMF solvent was added, 1.0 g of acrylic acid and 0.07 g of EDC·HCl were added, 1 M dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 5, and the mixture was stirred in an ice-water bath at 0-5°C for 3 h to fully dissolve the mixture, to obtain solution B; (3) the above solution A and solution B were mixed, stirred in an ice-water bath at 0-5°C for 10 h, filtered, washed with anhydrous ethanol for several times, and dried to obtain acrylic acid-modified carbon nanotubes CNT-AA-2; (4) 25.0 g of AM, 0.5 g of CNT-AA-2 and 1.6 g of C were added in a three-necked flask. 18DMAAC was completely dissolved in 100 ml of deionized water, and an appropriate amount of Na2CO3 was added to adjust the solution pH to 9. Nitrogen was passed through the mixture, and the mixture was stirred at 40°C and ultrasonically dispersed for 2 h. (5) 0.04 g K2S2O8 and 0.08 g NaHSO3 were added, and nitrogen was continued to be passed through and stirred until the viscosity of the solution increased significantly. Stirring and nitrogen were stopped, and the reaction was continued for 6 h. (6) The mixture was heated to 85°C and hydrolyzed with a mixture of NaOH and Na2CO3 for 4 h to obtain a black gel product. The product was granulated and repeatedly washed with acetone until a black solid was precipitated. The carbon nanotube grafted polymer nanoblocking agent CNT-HPAM-2 was obtained after drying at 70°C for 12 h.

[0053] Example 3

[0054] This embodiment provides a carbon nanotube grafted polymer nano plugging agent, and the preparation method thereof is as follows:

[0055] (1) 40 ml of DMF solvent was added, 0.1 g of CNT-NH2 and 0.1 g of SDS were added, and the mixture was stirred and ultrasonically dispersed for 2 h to obtain solution A; (2) 20 ml of DMF solvent was added, 1.0 g of acrylic acid and 0.05 g of EDC·HCl were added, 1 M dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 6, and the mixture was stirred in an ice-water bath at 0-5°C for 3 h to fully dissolve the mixture, to obtain solution B; (3) the above solution A and solution B were mixed, and the mixture was stirred in an ice-water bath at 0-5°C for 10 h, and then filtered and washed with anhydrous ethanol for several times, and dried to obtain acrylic acid-modified carbon nanotubes CNT-AA-3; (4) 25.0 g of AM, 0.8 g of CNT-AA-3 and 2.0 g of C were added in a three-necked flask. 18 DMAAC was completely dissolved in 100 ml of deionized water, and an appropriate amount of Na2CO3 was added to adjust the pH value of the solution to 10. The mixture was stirred at 40°C for 2 h and then ultrasonically dispersed. (5) 0.03 g K2S2O8 and 0.06 g NaHSO3 were added, and the nitrogen was continued to be stirred until the viscosity of the solution increased significantly. The stirring and nitrogen were stopped, and the reaction was continued for 4 h. (6) The mixture was heated to 70°C and hydrolyzed with a mixture of NaOH and Na2CO3 for 4 h to obtain a black gel product. The product was granulated and repeatedly washed with acetone until a black solid was precipitated. The carbon nanotube grafted polymer nanoblocking agent CNT-HPAM-3 was obtained after drying at 70°C for 12 h.

[0056] Example 4

[0057] This embodiment provides a carbon nanotube grafted polymer nano plugging agent, and the preparation method thereof is as follows:

[0058] (1) 40 ml of DMF solvent was added, 0.2 g of CNT-NH2 and 0.1 g of SDS were added, and the mixture was stirred and ultrasonically dispersed for 2 h to obtain solution A; (2) 20 ml of DMF solvent was added, 1.0 g of acrylic acid and 0.05 g of EDC·HCl were added, 1 M dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 4, and the mixture was stirred in an ice-water bath at 0-5°C for 3 h to fully dissolve the mixture, thereby obtaining solution B; (3) the above solution A and solution B were mixed, stirred in an ice-water bath at 0-5°C for 10 h, filtered, washed with anhydrous ethanol for several times, and dried to obtain acrylic acid-modified carbon nanotubes CNT-AA-4; (4) 25.0 g of AM, 0.2 g of CNT-AA-4 and 1.2 g of C were added in a three-necked flask. 18 DMAAC was completely dissolved in 100 ml of deionized water, and an appropriate amount of Na2CO3 was added to adjust the pH value of the solution to 8. Nitrogen was passed through the mixture, and the mixture was stirred at 40°C and ultrasonically dispersed for 2 h. (5) 0.03 g K2S2O8 and 0.06 g NaHSO3 were added, and nitrogen was continued to be passed through and stirred until the viscosity of the solution increased significantly. Stirring and nitrogen were stopped, and the reaction was continued for 6 h. (6) The mixture was heated to 90°C and hydrolyzed with a mixture of NaOH and Na2CO3 for 6 h to obtain a black gel product. The product was granulated and repeatedly washed with acetone until a black solid was precipitated. The carbon nanotube grafted polymer nanoblocking agent CNT-HPAM-4 was obtained after drying at 70°C for 12 h.

[0059] Example 5

[0060] This embodiment provides a carbon nanotube grafted polymer nano plugging agent, and the preparation method thereof is as follows:

[0061] (1) 40 ml of DMF solvent was added, 0.2 g of CNT-NH2 and 0.2 g of SDS were added, and the mixture was stirred and ultrasonically dispersed for 2 h to obtain solution A; (2) 20 ml of DMF solvent was added, 1.0 g of acrylic acid and 0.07 g of EDC·HCl were added, 1 M dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 5, and the mixture was stirred in an ice-water bath at 0-5°C for 3 h to fully dissolve the mixture, to obtain solution B; (3) the above solution A and solution B were mixed, and the mixture was stirred in an ice-water bath at 0-5°C for 10 h, and then filtered and washed with anhydrous ethanol for several times, and dried to obtain acrylic acid-modified carbon nanotubes CNT-AA-5; (4) 25.0 g of AM, 0.5 g of CNT-AA-5 and 1.6 g of C were added in a three-necked flask. 18DMAAC was completely dissolved in 100 ml of deionized water, and an appropriate amount of Na2CO3 was added to adjust the pH value of the solution to 9. Nitrogen was passed through the solution, and the solution was stirred at 40°C and ultrasonically dispersed for 2 h. (5) 0.04 g K2S2O8 and 0.08 g NaHSO3 were added, and the nitrogen was continued to be passed through the solution until the viscosity of the solution increased significantly. The stirring and nitrogen were stopped, and the reaction was continued for 4 h. (6) The temperature was raised to 70°C, and a mixture of NaOH and Na2CO3 was used for hydrolysis for 6 h to obtain a black gel product. The product was granulated and repeatedly washed with acetone until a black solid was precipitated. After drying at 70°C for 12 h, the carbon nanotube grafted polymer nanoblocking agent CNT-HPAM-5 was obtained.

[0062] Example 6

[0063] This embodiment provides a carbon nanotube grafted polymer nano plugging agent, and the preparation method thereof is as follows:

[0064] (1) 40 ml of DMF solvent was added, 0.2 g of CNT-NH2 and 0.4 g of SDS were added, and the mixture was stirred and ultrasonically dispersed for 2 h to obtain solution A; (2) 20 ml of DMF solvent was added, 1.0 g of acrylic acid and 0.1 g of EDC·HCl were added, 1 M dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 6, and the mixture was stirred in an ice-water bath at 0-5°C for 3 h to fully dissolve the mixture, thereby obtaining solution B; (3) the above solution A and solution B were mixed, stirred in an ice-water bath at 0-5°C for 10 h, filtered, washed with anhydrous ethanol for several times, and dried to obtain acrylic acid-modified carbon nanotubes CNT-AA-6; (4) 25.0 g of AM, 0.8 g of CNT-AA-6 and 2.0 g of C were added in a three-necked flask. 18 DMAAC was completely dissolved in 100 ml of deionized water, and an appropriate amount of Na2CO3 was added to adjust the solution pH to 10. The mixture was stirred at 40°C for 2 h and then ultrasonically dispersed. (5) 0.06 g K2S2O8 and 0.1 g NaHSO3 were added, and the nitrogen was continued to be stirred until the viscosity of the solution increased significantly. The stirring and nitrogen were stopped, and the reaction was continued for 4 h. (6) The temperature was raised to 85°C, and a mixture of NaOH and Na2CO3 was used for hydrolysis for 6 h to obtain a black gel product. The product was granulated and repeatedly washed with acetone until a black solid was precipitated. The carbon nanotube grafted polymer nanoblocking agent CNT-HPAM-6 was obtained after drying at 70°C for 12 h.

[0065] Example 7

[0066] The present embodiment provides a water-based drilling fluid. The raw materials of the water-based drilling fluid are, by mass percentage, 0.5% of the nano plugging agent CNT-HPAM-1 of Example 1, 0.5% of bentonite, 1.5% of a thickener, 2% of a fluid loss reducer, 1% of a pH regulator, 2% of a lubricant, an appropriate amount of a weighting agent (for adjusting the density of the water-based drilling fluid), and the remainder of water. The density of the water-based drilling fluid of the present embodiment is 1.7 g / cm 3 .

[0067] The preparation method of the water-based drilling fluid is as follows:

[0068] Bentonite was added to the water and stirred at a rate of 2500 rpm for 3 h to fully hydrate the bentonite; then a viscosity enhancer, a fluid loss reducer, a pH adjuster, a lubricant, and a nano plugging agent CNT-HPAM-1 were added, and finally a weighting agent was added to adjust the density of the drilling fluid. After uniform mixing, a water-based drilling fluid C1 was obtained.

[0069] Example 8

[0070] The present embodiment provides a water-based drilling fluid. The raw materials of the water-based drilling fluid are, by mass percentage, 2% of the nano plugging agent CNT-HPAM-1 of Example 1, 1% of bentonite, 1% of a viscosity enhancer, 1.5% of a fluid loss reducer, 1% of a pH regulator, 2% of a lubricant, an appropriate amount of a weighting agent (for adjusting the density of the water-based drilling fluid), and the remainder of water.

[0071] The density and preparation method of the water-based drilling fluid of this embodiment are the same as those of Embodiment 7. The water-based drilling fluid is denoted as C2.

[0072] Example 9

[0073] The present embodiment provides a water-based drilling fluid. The raw materials of the water-based drilling fluid are, by mass percentage, 3% of the nano plugging agent CNT-HPAM-1 of Example 1, 1.5% of bentonite, 0.5% of a viscosity enhancer, 1.5% of a fluid loss reducer, 1% of a pH adjuster, 2% of a lubricant, an appropriate amount of a weighting agent (for adjusting the density of the water-based drilling fluid), and the remainder of water.

[0074] The density and preparation method of the water-based drilling fluid of this embodiment are the same as those of Embodiment 7. The water-based drilling fluid is denoted as C3.

[0075] Example 10

[0076] This embodiment provides a water-based drilling fluid, which is the same as that of embodiment 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced by the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-2 prepared in embodiment 2. The water-based drilling fluid is denoted as B1.

[0077] Embodiment 11

[0078] This embodiment provides a water-based drilling fluid, which is the same as that of embodiment 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced by the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-3 prepared in embodiment 3. The water-based drilling fluid is denoted as B2.

[0079] Example 12

[0080] This embodiment provides a water-based drilling fluid, which is the same as that of embodiment 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced by the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-5 prepared in embodiment 5. The water-based drilling fluid is denoted as B3.

[0081] Comparative Example 1

[0082] This comparative example provides a water-based drilling fluid, which is the same as Example 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced with a common plugging agent ultrafine calcium carbonate in this comparative example. The water-based drilling fluid is recorded as D1.

[0083] Comparative Example 2

[0084] This comparative example provides a water-based drilling fluid, which is the same as Example 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced with commercially available amino-functionalized multi-walled carbon nanotubes in this comparative example. The water-based drilling fluid is recorded as D2.

[0085] Comparative Example 3

[0086] This comparative example provides a water-based drilling fluid, which is the same as Example 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is not added in this comparative example. The water-based drilling fluid is recorded as D3.

[0087] Comparative Example 4

[0088] This comparative example provides a water-based drilling fluid, which is the same as Example 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced by the acrylic acid modified carbon nanotube CNT-AA-1 of Example 1. The water-based drilling fluid is recorded as D4.

[0089] Comparative Example 5

[0090] This comparative example provides a water-based drilling fluid, which is the same as Example 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced by a mixture of amino-functionalized multi-walled carbon nanotubes and polyacrylamide in a mass ratio of 0.1:25 in this comparative example. The water-based drilling fluid is recorded as D5.

[0091] Comparative Example 6

[0092] This comparative example provides a water-based drilling fluid, which is the same as Example 8, except that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-1 is replaced with a common shale inhibitor RF-9 in this comparative example. The water-based drilling fluid is recorded as D6.

[0093] Experimental Example 1 Particle Size Test

[0094] The six carbon nanotube grafted polymer nano plugging agents prepared in Examples 1-6, the acrylic acid modified carbon nanotube CNT-AA-2 prepared in Example 2, and the raw material CNT-NH2 were added to pure water in an amount of 1 wt %, and then allowed to stand at 120° C. The particle size distribution of different nanomaterials in pure water was tested using a particle size analyzer within 60 days. The results are shown in Table 1.

[0095] Table 1 Particle size distribution of various nanomaterials at 120°C for 60 days

[0096]

[0097]

[0098] It can be seen from Table 1 that the minimum particle size of CNT-HPAM-1, CNT-HPAM-2, CNT-HPAM-3, CNT-HPAM-4, CNT-HPAM-5, CNT-HPAM-6, CNT-NH2, and CNT-AA-2 materials changed little, and the average particle size changed by 5.67%, 5.25%, 5.54%, 4.78%, 6.11%, 5.67%, 6.42%, 58.3%, and 18.5% within 60 days, indicating that the carbon nanotube grafted polymer nanoplugging agent has good high-temperature stability.

[0099] Experimental Example 2 Infrared Spectrum Structure Characterization

[0100] In this experimental example, the infrared spectroscopy structure of the three nanomaterials CNT-NH2, CNT-AA-1, and CNT-HPAM-1 in Example 1 was characterized. Figure 1 shown.

[0101] from Figure 1 It can be seen that the infrared spectrum of CNT-NH2 is located at 3060cm -1and 2947cm -1 The two characteristic absorption peaks are the stretching vibration peaks of NH, 1700-1500cm -1 The characteristic absorption peak at 1009cm is the in-plane bending vibration peak of NH. -1 The characteristic absorption peaks on the left and right are the shear vibration peaks of NH, 1072cm -1 The characteristic absorption peaks on the left and right are the stretching vibration peaks of CN, 910-650cm -1 The characteristic absorption peak at is the out-of-plane bending vibration peak of NH.

[0102] In the infrared spectrum of CNT-AA-1, the -1 The characteristic absorption peak at 1662 cm is the stretching vibration peak of NH. -1 The characteristic absorption peak at 1433 cm is the stretching vibration peak of C=O. -1 The characteristic absorption peak at 978cm is the stretching vibration peak of CN. -1 The absorption peak at 910-650cm is the characteristic peak of monosubstituted olefins. -1 The characteristic absorption peak at is the out-of-plane bending vibration peak of NH. In addition, C=C is located at 1680-1620cm -1 The stretching vibration peak of is weak and may be covered by the stretching vibration peak of C=O.

[0103] In the infrared spectrum of CNT-HPAM-1, at 3325 cm -1 and 3192cm -1 The characteristic absorption peaks at the two locations are the stretching vibration peaks of NH, 2939 cm -1 The characteristic absorption peak at 1672 cm is the stretching vibration peak of CH in ammonium salt. -1 The characteristic absorption peak at 1560 cm is the stretching vibration peak of C=O in the amide group. -1 The characteristic absorption peak at 1410 cm is the plane bending vibration peak of NH. -1 and 1314cm -1 The characteristic absorption peaks at the two locations are the stretching vibration peaks of CN in the amide group, 1192 cm -1 and 1124cm -1 The characteristic absorption peaks at the two locations are the stretching vibration peaks of CN in the ammonium salt, 789 cm -1 and 663cm -1 The two characteristic absorption peaks are the out-of-plane bending vibration peaks of NH.

[0104] Therefore, infrared spectrum analysis can confirm that the present invention successfully synthesized acrylic acid modified carbon nanotubes (CNT-AA) and carbon nanotube grafted polymer nano plugging agent (CNT-HPAM)

[0105] Experimental Example 3 Salt tolerance test

[0106] Zeta potential is an important indicator for characterizing the stability of colloidal dispersions. In this experimental example, the salt resistance of the CNT-HPAM-2 material of Example 2 was evaluated by Zeta potential analysis.

[0107] CNT-HPAM-2 material was added to deionized water, saturated brine and simulated formation water respectively, with an addition amount of 1wt%, and fully stirred. Then, the solution was left to stand for 28 days, and the Zeta potential changes of the three solutions within 28 days were tested. The results are as follows: Figure 2 shown.

[0108] according to Figure 2 It can be seen that the carbon nanotube grafted polymer nano plugging agent CNT-HPAM-2 has excellent stability and salt resistance.

[0109] Experimental Example 4: Plugging Performance Test

[0110] Based on Experimental Example 3, this Experimental Example further evaluates the plugging performance of the water-based drilling fluids in Examples 7-12 and Comparative Examples 1-3.

[0111] Drilling fluids were prepared according to Examples 7-12 and Comparative Examples 1-3. The density of each water-based drilling fluid was 1.7 g / cm 3 The aging temperature is 120℃ and the aging time is 24h. After aging, the viscosity, dynamic shear force and high temperature and high pressure filtration loss of the water-based drilling fluid were tested, and the results are shown in Table 2.

[0112] Table 2 Plugging performance of water-based drilling fluid

[0113]

[0114]

[0115] As shown in Table 2, the water-based drilling fluid maintains good rheological properties after aging at 120°C. Compared with the drilling fluids with the addition of common plugging agent ultrafine calcium carbonate (D1), amino-functionalized multi-walled carbon nanotubes (D2), no plugging agent (D3), acrylic acid-modified carbon nanotubes (D4), amino-functionalized multi-walled carbon nanotubes and polyacrylamide mixture (D5) and common shale inhibitor RF-9 (D6), the drilling fluids with the addition of carbon nanotube grafted polymer nano plugging agent CNT-HPAM (C1-C3, B1-B3) have significantly reduced filtration loss, among which the filtration loss of B1 is as low as 2.1 mL, which shows that the nano plugging agent improves the plugging property of the water-based drilling fluid.

Claims

1. A method for preparing a carbon nanotube grafted polymer nano plugging agent, comprising the following steps: S1: reacting acrylic acid with amino-functionalized multi-walled carbon nanotubes to generate acrylic acid-modified carbon nanotubes; wherein: The mass ratio of acrylic acid to amino-functionalized multi-walled carbon nanotubes is 1:0.1-0.2; S2: copolymerizing acrylamide, the acrylic acid modified carbon nanotubes and octadecyl dimethyl allyl ammonium chloride to obtain the carbon nanotube grafted polymer nano plugging agent; wherein the mass ratio of acrylamide, the acrylic acid modified carbon nanotubes and octadecyl dimethyl allyl ammonium chloride is 25:0.2-0.8:1.2-2.

0.

2. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 1, wherein: S1 includes the following steps: (1) adding amino-functionalized multi-walled carbon nanotubes and sodium dodecyl sulfate to N,N-dimethylformamide and performing ultrasonic dispersion to obtain a carbon nanotube solution A; (2) adding acrylic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N,N-dimethylformamide, adding hydrochloric acid dropwise to adjust the pH value of the solution to 4-6, stirring and dissolving the solution to obtain acrylic acid solution B; (3) The carbon nanotube solution A and the acrylic acid solution B are mixed and reacted to obtain a solid product, which is then filtered and washed to obtain the acrylic acid-modified carbon nanotubes.

3. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 2, wherein: The mass ratio of amino-functionalized multi-walled carbon nanotubes, acrylic acid, sodium dodecyl sulfate and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 0.1-0.2:1:0.1-0.4:0.05-0.

1.

4. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 2, wherein: The reaction temperature of step (3) is 0-5°C and the reaction time is 8-10h; Preferably, the dissolution process of step (2) is carried out at 0-5°C; Preferably, the reagent used for washing in step (3) is ethanol.

5. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 1, wherein: S2 includes the following steps: (4) dissolving acrylamide, the acrylic acid-modified carbon nanotubes, and octadecyldimethylallyl ammonium chloride in water, adjusting the pH value to 8-10, introducing nitrogen gas, and performing ultrasonic dispersion to obtain a dispersion; (5) adding an initiator to the dispersion, continuing to pass nitrogen and stirring until the viscosity of the solution increases; then stopping stirring and passing nitrogen, and continuing the reaction to obtain a reaction solution; (6) Heating the reaction solution, adding alkaline solution to carry out hydrolysis reaction to obtain a gel product, and washing and drying to obtain the carbon nanotube grafted polymer nano plugging agent.

6. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 5, wherein: The initiator is a mixture of potassium persulfate and sodium bisulfite.

7. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 6, wherein: The mass ratio of potassium persulfate, sodium bisulfite and acrylamide is 0.03-0.06:0.06-0.1:

25.

8. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 5, wherein: The reaction time in step (5) is 4-6 hours.

9. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 5, wherein: In step (6), the reaction solution is heated to 70-90° C. and the hydrolysis reaction time is 4-6 hours.

10. The method for preparing the carbon nanotube grafted polymer nano plugging agent according to claim 5, wherein: In step (6), the alkali solution is sodium hydroxide and / or sodium carbonate; Preferably, the reagent used for washing is acetone; Preferably, the drying conditions are: drying at 60-80°C for 10-15h.

11. A carbon nanotube grafted polymer nano plugging agent, which is obtained by the preparation method of the carbon nanotube grafted polymer nano plugging agent according to any one of claims 1 to 10.

12. The carbon nanotube grafted polymer nano plugging agent according to claim 11, wherein: The particle size distribution of the carbon nanotube grafted polymer nano plugging agent is between 16-451 nm.

13. A water-based drilling fluid comprising the carbon nanotube grafted polymer nano plugging agent according to claim 11 or 12.

14. The water-based drilling fluid according to claim 13, wherein: The raw materials of the water-based drilling fluid include, by mass percentage, 0.5-3% of the carbon nanotube grafted polymer nano plugging agent, 0.5-1.5% of bentonite, 0.5-1.5% of viscosity enhancer, 1.0-2.0% of fluid loss reducer, 0.5-1.5% of pH regulator, 2.0-4.0% of lubricant, and the balance of water.

15. The water-based drilling fluid according to claim 14, wherein: The raw materials of water-based drilling fluid also include weighting agents. The density of water-based drilling fluid with weighting agents added is 1.2-2.0g / cm 3 .

Citation Information

Patent Citations

  • Nanometer plugging agent for water-based drilling fluid, preparing method of nanometer plugging agent and drilling fluid

    CN109825263A

  • Carbon nanotube hybridized heat-resistant and salt-tolerant polymer and preparing method thereof

    CN110003409A

  • Flexible-outside rigid-inside multi-walled carbon nanotube nano plugging agent and oil-based drilling fluid

    CN114214047A

  • Bionic and amphiphobic high-efficiency water-based drilling fluid

    CN114350332A

  • High-temperature-resistant hydrophobic nano blocking agent for water-based drilling fluid as well as preparation method and application of high-temperature-resistant hydrophobic nano blocking agent

    CN115260404A